When More Data Hurts: A Troubling Quirk in Developing Broad-Coverage Natural Language Understanding Systems - Stengel-Eskin, Elias; Platanios, Emmanouil Antonios; Pauls, Adam; Thomson, Sam; Fang, Hao; Van Durme, Ben; Eisner, Jason; Su, Yu (EMNLP 2022, 2022)
In natural language understanding (NLU) production systems, users’ evolving needs necessitate the addition of new features over time, indexed by new symbols added to the meaning representation space. This requires additional training data and results in ever-growing datasets. We present the first systematic investigation into this incremental symbol learning scenario. Our analysis reveals a troubling quirk in building broad-coverage NLU systems: as the training dataset grows, performance on a small set of new symbols often decreases. We show that this trend holds for multiple mainstream models on two common NLU tasks: intent recognition and semantic parsing. Rejecting class imbalance as the sole culprit, we reveal that the trend is closely associated with an effect we call source signal dilution, where strong lexical cues for the new symbol become diluted as the training dataset grows. Selectively dropping training examples to prevent dilution often reverses the trend, showing the over-reliance of mainstream neural NLU models on simple lexical cues.